1992
DOI: 10.2140/pjm.1992.155.251
|View full text |Cite
|
Sign up to set email alerts
|

On the postulation of 0-dimensional subschemes on a smooth quadric

Abstract: If X is a O-dimensional subscheme of a smooth quadric Q = P 1 x P 1 we investigate the behaviour of X with respect to the linear systems of divisors of any degree (a, b). This leads to the construction of a matrix of integers which plays the role of a Hubert function of X we study numerical properties of this matrix and their connection with the geometry of X. Further we relate the graded Betti numbers of a minimal free resolution of X on Q with that matrix, and give a complete description of the arithmeticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 7 publications
2
73
0
Order By: Relevance
“…In this situation there are several classifications. Giuffrida, Maggioni, and Ragusa [7], who helped to initiate the study of points in multiprojective spaces (see, for example [8,9,12,13,14,18,20,21,22] for more on these points), provided the first classification. They showed that ACM sets of points in P 1 × P 1 can be classified via their Hilbert functions.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation there are several classifications. Giuffrida, Maggioni, and Ragusa [7], who helped to initiate the study of points in multiprojective spaces (see, for example [8,9,12,13,14,18,20,21,22] for more on these points), provided the first classification. They showed that ACM sets of points in P 1 × P 1 can be classified via their Hilbert functions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only ACM sets of (fat) points in P 1 × P 1 have been classified. ACM sets of points in P 1 × P 1 were first classified via their Hilbert function in [9]. An alternative classification was provided by the second author [22], which we recall here.…”
Section: Acm Points and Fat Pointsmentioning
confidence: 99%
“…Because λ = (6, 5, 3, 1, 1), it follows that α Y = (12,11,9,7,7,6,5,3,1,1). Then the shifts in the bigraded minimal free resolution of I Y are given by SY 0 = {(10, 0), (8, 1), (7, 3), (6,5), (5,6), (3,7), (2,9), (1,11), (0, 12)} SY 1 = {(10, 1), (8, 3), (7,5), (6,6), (5,7), (3,9), (2,11), (1, 12)}.…”
Section: The Completion Of Zmentioning
confidence: 99%
“…Recently, many authors (cf. [4,[9][10][11]16]) have been interested in extending our understanding of points in P n to sets of points in P n1 × · · · × P n k . We continue this trend by studying reg(I ) when I deÿnes a scheme of fat points in P n1 × · · · × P n k .…”
Section: Introductionmentioning
confidence: 99%